Керування режимом роботи електростанції з відновлюваними джерелами енергії в умовах зміни частоти в енергосистемі - Кириленко, О.В.; Павловський, В.В.; Яндульський, О.С.; Стелюк, А.О. (Технічна електродинаміка, 2012)
The aspects of the power system operation with the renewable energy sources (RES) have been considered. The participation of RES in the frequency control according to the grid code requirements of Transmission System Operators of the power systems with considerable RES penetration has been analyzed. The control subsystem structure of such power-plants is proposed in the event of changing frequency.